Efficacy of Antiviral Treatment in Liver Biopsy-Proven Immune-Tolerant Chronic Hepatitis B Patients: A Retrospective Cohort Study - Liu, Na; Yang, Nan; Ma, Wenqi; Yang, Shujuan; Hu, Chunhua; Li, Juan; Zhao, Yingren; Xu, Guanghua; He, Yingli (Frontiers in Medicine, 2021)
The optimal timing of initiating antiviral treatment for immune-tolerant (IT) patients remains unknown. We conducted this study in liver biopsy-proven IT patients to compare the long-term outcomes of untreated and treated patients suffering non-cirrhotic chronic hepatitis B (CHB). This retrospective cohort study recruited 171 consecutive treatment-naïve CHB patients who completed liver biopsy test. Patients were stratified into IT (n = 60), mildly-active (MA; n = 31), immune-active (IA; n = 80), according to alanine aminotransferase (ALT) and liver biopsy data. One hundred and nine patients receiving antiviral treatment constituted the treated set, and 62 patients under close follow-up comprised the untreated set. Primary outcomes were virological response, HBeAg seroconversion, HBsAg loss, ALT normalization, and liver stiffness measurement normalization (NCT03740789). The study population was predominantly male (62.6%) with a mean age of 31 years. The proportion of virological response in treated patients in the MA phase was 57.1%, and the proportion of HBeAg seroconversion was 28.6%, which showed no difference with the 43.8% virological response and 31.5% HBeAg seroconversion in IA patients. The proportions of virological response and seroconversion were 18.2 and 9.1%, respectively, in the IT phase, which were lower than the rates in the MA and IA phases. However, 95.5% of IT patients persisted normal ALT, and 100% of IT patients persisted normal liver stiffness measurement in the treated group. Therefore, antiviral treatment should be considered for CHB patients with high viral load regardless of phase to minimize further damage to hepatocytes.